La gestión de tesorería y toma de decisiones en la Gerencia Sub Regional de Ucayali Contamana año 2022 - Malasquez Sajami, Jean Piere (2022)
The general objective of the research was to determine the relationship between treasury management and decision making in the Sub Regional Management of Ucayali Contamana year 2022, where an applied type study, correlational level and non-experimental design was chosen, which was formed by 122 workers, with a sample of 93 workers, the same ones who were surveyed using the survey technique, using a questionnaire of questions. Therefore, it has been concluded that treasury management is qualified as regular (23%) because it almost never has a procedures manual that regulates the financial execution of income, but sometimes the checks are drawn in the name of the person in charge. of fund administration, as well as sometimes there is a directive for the administration of the fund for cash payments. On the other hand, decision making is qualified as regular (27%) because the lack of integrity is sometimes the main problem in the institution, just as the manager sometimes needs the financial statements to make decisions, however, almost never. seeks specialized advice for the optimal development of a final decision. Finally, it has been determined that there is a significant relationship between treasury management and decision making, which was contrasted by a coefficient of 0.817, which is at a considerable positive level with a (bilateral) significance of 0.000.